Bioethics and Patent Law: USA, UK and India. A Bibliometric Analysis - Gupta, Mona; Srivastava, Divya; Kushwah, Arvind Singh (Bangladesh Journal of Bioethics, 2013)
This article discusses the view of bioethics in terms of need of research and gives more weight to various cultural traditions and their respective moral beliefs. It is argued that this view is implausible for the following three reasons: it renders the disciplinary boundaries of bioethics too flexible and inconsistent with metaphysical commitments of biomedical sciences, it is normatively useless because it approaches cultural phenomena in a predominantly descriptive and selective way, and it tends to justify certain types of discrimination. Compromise on moral matters attracts ambivalent reactions, since it seems at once laudable and deplorable. When a hotly-contested phenomenon like assisted dying is debated, all-or-nothing positions tend to be advanced, with little thought given to the desirability of, or prospects for, compromise. In order to qualify as appropriately principled, the ensuing negotiations require disputants to observe three constraints: they should be suitably reflective, reliable and respectful in their dealings with one another. The product that will result from such a process will also need to split the difference between the warring parties. In assisted dying, I argue that a reduced offence of 'compassionate killing' can achieve this. Clinical research is revolutionizing the practice of medicine in an unprecedented way. Some current legal and ethical concerns evolving from this revolution are addressed, pointing to the emerging concepts in jurisprudence, which regards medical research as an important contribution to patient empowerment, to medical risk management and in managing the resources of a national health system. While bioethics as a field has concerned itself with methodological issues since the early years, there has been no systematic examination of how ethics is incorporated into research on the ethical, legal and social implications. We aim of better understanding the methods, aims, and approaches to ethics that its researchers employ. We found that the aims of ethics are largely prescriptive and address multiple groups. This is a life concern issue. It is an important issue for researchers, teachers as well as for student. This articles main aim is to provide systematic outline of the complex relationship between bioethics and patent between India, USA and UK. This study suggests that trusting relationships may be more conducive than any particular discussion strategy to facilitating doctor-patient discussions of health care costs. Better public understanding of how medical decisions affect insurer costs and how such costs ultimately affect patients personally will be necessary if discussions about insurer costs are to occur in the clinical encounter. It will give an overview of the bioethics and Patent. The literature survey has indicated that there is no comprehensive work has been done by any researcher on this topic. Therefore the present study would concentrate on the work being carried out by Indian, USA and UK R & D scientists vis-a-vis Global researchers. Studies aims to map basic human needs such as human health, food and a safe environment, touches on fundamental values, such as human dignity and the genetic integrity of humanity, can raise human rights issues such as access to health and benefits from scientific progress, raises concerns over equitable access to the fruits of new technologies, the consent of those involved in research, and protection of the environment and compare these among India, USA and UK. The research map out many issues and policy communities, but main aspect is the ethical implications of protecting biotechnological inventions through the intellectual property (IP) system. A Bioethicist assists the health care and research community in examining moral issues involved in our understanding of life and death, and resolving ethical dilemmas in medicine and science. This research provides a systematic outline of the complex relationship between bioethics and IP. It will give an overview of bioethics. It sketches core principles in the interaction of IP and bioethics among these three countries. The basic data for the bibliometric analysis has been collected from SCI and for mapping different parameters suitable analytical software eg. SPSS, BibTech Mon is used. The analysis arises questions such as: Does India do enough work in this field. Which country is fastest growth among these? DOI: http://dx.doi.org/10.3329/bioethics.v4i2.16371 Bangladesh Journal of Bioethics 2013; 4(2) 1-8